Cardiopulmonary Arrest Caused by Large Substernal Goiter—Treatment with Combined Cervical Approach and Median Mini-Sternotomy: Report of a Case - Charilaos Koulouris (Medicina, 2021)
Introduction: Substernal goiter is usually defined as a goiter that extends below the thoracic inlet or a goiter with more than 50% of its mass lying below the thoracic inlet. Substernal goiters may compress adjacent anatomical structures causing a variety of symptoms. Case report: Here we report a rare case of a 75-year-old woman presenting with cardiac arrest caused by acute respiratory failure due to tracheal compression by a substernal goiter. Discussion: Substernal goiters can be classified as primary or secondary depending on their site of origin. Symptoms are diverse and include a palpable neck mass, mild dyspnea to asphyxia, dysphagia, dysphonia, and superior vena cava syndrome. Diagnosis of substernal goiter is largely based on computed tomography imaging, which will show the location of the goiter and its extension in the thoracic cavity. Surgery is the treatment of choice for symptomatic patients with substernal goiter. The majority of substernal goiters are resected through a cervical approach. However, in approximately 5% of patients, a thoracic approach is required. The most important factor determining whether a thoracic approach should be used is the depth of the extension to the tracheal bifurcation on CT imaging. Conclusion: Cardiac arrest appearing as the first symptom of a substernal goiter is a very rare condition and should be treated by emergency thyroidectomy via a cervical or thoracic approach depending on the CT imaging findings.